POSSIBLE APPLICATION OF BIOHPP IN PROSTHETIC DENTISTRY: A LITERATURE REVIEW - Jivko Georgiev; Angelina Vlahova; Hristo Kissov; Svetlin Aleksandrov; Rada Kazakova (Peytchinski Publishing, 2018)
Purpose: The aim of this presentation is to summarize the clinical applications of BioHPP (High Performance Polymer) for removable and fixed restorations. Materials and methods: A critical survey was conducted among 299 literature sources related to PEEKs and in particular with BioHPP. Results and discussion: According to the literature in this field the mechanical properties (in particular its elasticity) of BioHPP are closer to those of the dental tissues, and this fact gives an advantage of this material compared to the metal alloys and the ceramics. A variety of procedures have been suggested to condition the surface of BioHPP in order to facilitate its bonding with resin composite cements. In the Prosthetic Dentistry BioHPP is widely used for fixed and removable restorations frameworks fabrication by pressing and by CAD/CAM technology. Conclusion: Nowadays investigations for new abilities of BioHPP use in Prosthodontics are conducted. They are based on combined alternative fixed restorations made of PEEKs and metal alloys.